2020
DOI: 10.2298/tsci180102151a
|View full text |Cite
|
Sign up to set email alerts
|

Computational fluid simulation of non-Newtonian two-phase fluid flow through a channel with a cavity

Abstract: In this paper, the numerical solution of non-Newtonian two-phase fluid-flow through a channel with a cavity was studied. Carreau-Yasuda non-Newtonian model which represents well the dependence of stress on shear rate was used and the effect of n index of the model and the effect of input Reynolds on the attribution of flow were considered. Governing equations were discretized using the finite volume method on staggered grid and the form of allocating flow parameters on staggered grid is based on marker and cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Two-dimensional laminar mixed convection in a hollow connected to a horizontal channel was investigated statistically by Ahmadi and Farsani [15]. A cavity-enclosed conduit was subjected to a two-phase flow of a non-Newtonian fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional laminar mixed convection in a hollow connected to a horizontal channel was investigated statistically by Ahmadi and Farsani [15]. A cavity-enclosed conduit was subjected to a two-phase flow of a non-Newtonian fluid.…”
Section: Introductionmentioning
confidence: 99%
“…While there are those who acknowledge the existence of this effect [14,15]. Ahmadi, et al [16] studied two-phase flow and cavity through a channel using computational analysis and investigated the effect of input Reynolds and flow properties. Aungi and Yuwono [17] reported that the multiphase flow pattern through and around the elbow bend was perhaps more dependent on liquid superficial velocity and also affected by gas volume fraction at high liquid velocity for the same operation condition.…”
Section: Introductionmentioning
confidence: 99%
“…A stereoscopic time-resolved particle image velocimetry (TR-PIV) was used to assess the thermal effects on the flow.They concluded that the increase in Re lowers the critical Richardson number above which the flow was no longer encapsulated. Ahmadi and Farsani[39], 2020, involved the non-Newtonian fluid in a 2D laminar mixed convection in a cavity linked with a horizontal channel. A non-Newtonian two phase fluid flow was entered the channel with the cavity.…”
mentioning
confidence: 99%